2009
DOI: 10.1002/elan.200804480
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of o‐Nitrophenol at Hexagonal Mesoporous Silica Modified Carbon Paste Electrodes

Abstract: A hexagonal mesoporous silica (HMS) modified carbon paste electrode (CPE) was fabricated and characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) methods (ferrocene as a probe). The electrochemical behavior of nitrophenol (o-NP) at the HMS modified electrode (HMSCPE) was investigated. Compared with CPE, a well-defined reduction peak and a remarkably peak current response was observed. It is indicated that mesoporous HMS exhibited remarkable enhancement effects on the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The value of the slopes for OA and TA is close to an expected Nernstian slope. On the other hand, according to the following formula [ 47 ]: where m and n are the participating number of protons and electron transfer number in the reaction respectively. The ratio of m/n at ERGO/GCE was calculated to be approximately 1, suggesting that the equal numbers of protons and electrons were transferred in both electrochemical oxidation reactions of OA and TA.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the slopes for OA and TA is close to an expected Nernstian slope. On the other hand, according to the following formula [ 47 ]: where m and n are the participating number of protons and electron transfer number in the reaction respectively. The ratio of m/n at ERGO/GCE was calculated to be approximately 1, suggesting that the equal numbers of protons and electrons were transferred in both electrochemical oxidation reactions of OA and TA.…”
Section: Resultsmentioning
confidence: 99%
“…The linear regression equation can be expressed as E pc (V) = À0.045pH À 0.364 (R 2 = 0.9925). According to the following formula of dE pc / dpH = (2.303mRT)/(nF) [46], where m is the number of proton, n is the number of electron, R, T and F have their usual meanings. Thus, the proton transfer number (m) was calculated to be 2, suggesting that the electrochemical reduction of 4-NP on the PDDA-G/GCE should be a two-electron and two-proton process.…”
Section: Ph Effectmentioning
confidence: 99%
“…A good linear relationship between E pa and pH was constructed (a) with a linear regression equation expressed as E pa = 0.4955–0.0623 pH, R 2 = 0.9969 ( E pa : V). According to Nernst equation E pa = E θ − [(2.303 mRT)/(nF)] pH [38, 40], the ratio of m / n was calculated as 1.06; this finding showed that the numbers of transferred electrons and protons were equal during the electrode reaction, and the result was consistent with those in previous reports [14, 16]. Moreover, the maximum oxidation peak current was achieved at pH 3.0 (b).…”
Section: Resultsmentioning
confidence: 99%